2001
DOI: 10.1562/0031-8655(2001)074<0765:iouasi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of UVB-absorbing Sunscreen Ingredients with Cutaneous Molecules May Alter Photoimmune Protection¶

Abstract: Studies of the photoimmunoprotective properties of sunscreens have produced disparate results. In this study in hairless mice, we compared two UVB absorbers, 2-ethylhexyl-p-methoxycinnamate (2-EHMC) and octyl-N-dimethyl-p-aminobenzoate (o-PABA), individually formulated in a common base lotion with a sunburn protection factor of 6. We measured their capacity to protect against suppression of the contact hypersensitivity (CHS) induced by three daily exposures of the dorsum to 6x the minimal erythemal/edematous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…(18) found that SSUV irradiation of human subjects through a broad‐spectrum sunscreen was significantly less protective against the formation of DNA lesions (cyclobutane pyrimidine dimers and 8‐hydroxy‐2′‐deoxyguanosine) and the expression of the tumor suppressor p53 than irradiation through a UVB‐only absorbing sunscreen matched for sun protection factor. These differing findings are difficult to explain, but the nature of the UV‐absorbers, their photostability (19), their possible interaction with skin components (20), the fluence and spectral properties of the UV doses delivered through them and the indicators measured to assess immune function may be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…(18) found that SSUV irradiation of human subjects through a broad‐spectrum sunscreen was significantly less protective against the formation of DNA lesions (cyclobutane pyrimidine dimers and 8‐hydroxy‐2′‐deoxyguanosine) and the expression of the tumor suppressor p53 than irradiation through a UVB‐only absorbing sunscreen matched for sun protection factor. These differing findings are difficult to explain, but the nature of the UV‐absorbers, their photostability (19), their possible interaction with skin components (20), the fluence and spectral properties of the UV doses delivered through them and the indicators measured to assess immune function may be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…SSUV rudiurion. The SSUV (290-400 nm) source for irradiation of the mice has been described previously (22) and comprised a cellulose acetatefiltered planar bank of six fluorescent UV-A-emitting tubes (Hitachi 40W F40T lO/BL black light, Tokyo, Japan) flanking one UV-B-emitting tube (Philips TL 40W/12RS, Eindhoven, The Netherlands). Mice were irradiated unrestrained in their boxes, with the wire cage tops removed.…”
Section: Methodsmentioning
confidence: 99%
“…The base lotion used as the vehicle for PycnogenolC? or cis-UCA was a simple oil-in-water cosmetic emulsion prepared without preservatives, perfume or coloring agents and known to be innocuous on the mouse skin (22). PycnogenolB extract (Horphag Research Ltd, Geneva, Switzerland) was dissolved in dimethyl sulfoxide (DMSO) at concentrations up to 4% wt/vol and diluted with base lotion to produce lotions containing 0.02542% wt/vol of the extract and 5% vol/vol DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations